The Methods and Criterion of Origen and Maximus Confessors Exegesis in Interpreting Scriptures Verses on Violence: its Relevance to Prevent Radicalism and Fundamentalism - Agus Widodo (P3TK, Sanata Dharma University, 2020)
Radicalism and fundamentalism, commonly characterized by acts of terror and violence, are considered as serious threats to Indonesia as a nation. One of the triggers of radical and fundamentalist movements is the misunderstanding on some verses about violence, war, and murder in the Scriptures. The radicals and the fundamentalists tend to interpret literally and use those verses to legitimate their actions. This paper has no intention to blame and to correct verses of the Scriptures that are literally provocative for violence, but to offer some inspiration from patristic tradition about how to interpret the Bible verses on violence. There are three methods and one criterion, that is, method of esegesi orante, method of allegorical-spiritual, method of the Scripture interprets Scripture, and the criteria of ??????? (?phleia: benefit). These methods and criterion may also be applied to interpret and to understand Koran verses on violence, as there are some provocative verses in regard to violence in both Scriptures. Moreover, Muslims also have the Tafsir (exegesis, commentary) as a methodology for reading and explaining the Koran, even accepting hermeneutics as a method of interpretation that is very relevant to understand the message of the Koran.DOI:doi.org/10.24071/jaot.2020.020101